Higher order thinking implementation strategies in teaching listening and speaking skills of Malay language teachers in primary school - Abdul Aziz, Farah Aziana; Abdul Rahman, Fadzilah; Othman, Shamsudin (Human Resource Management Academic Research Society, 2020)
Higher Order Thinking Skills (HOT) is one of the key elements that are emphasized in the Malaysia Education Blueprint (MEB) 2013-2025 to improve the quality of the country’s education which comparable with other countries. Most of Malay language teachers are facing shortage of HOT teaching strategies specifically in PdPc. In this regard, a study on HOT implementation strategy should be executed to address the gaps in the study of HOT. In this study, the research method used was qualitative since previous studies on HOT had used quantitative method. The method of direct observation of classroom teaching, semi-structured interviews and document analysis were used in this study. Specifically, this study covers four main objectives, which were to describe the implementation strategies of HOT in PdPc listening and speaking skills in Selangor Integrated Primary Religious School at the level of thought of applying, analyzing, evaluating and creating. The researchers used the case study research design, which the case on HOT implementation strategies in Malay language teachers’ teaching listening and speaking skills at Integrated Primary Religious School. Six respondents were chosen from three different Integrated Primary Religious Schools, where they teach standard 5 Malay language, covering both urban and rural areas. Anderson and Krathwohl Bloom's Taxonomy Theory Revised (2001) and Robert Glaser's Teaching Model (1962) were used to answer each question in this study. The findings showed that out of 28 HOT strategies, 14 HOT implementation strategies occured in PdPc listening and speaking skills. The results reported that almost all the six participants conducted HOT teaching started with the determination of the teaching objectives, which based on the existing knowledge of the students, the used of appropriate HOT teaching methods and the assessment of the well-conducted PdPc.